Definition and clinical significance of tumour rupture in gastrointestinal stromal tumours of the small intestine. Issue 6 (14th March 2016) - Hølmebakk, T.; Bjerkehagen, B.; Boye, K.; Bruland, Ø.; Stoldt, S.; Sundby Hall, K.
Abstract: Background: Tumour rupture is a risk factor for recurrence of gastrointestinal stromal tumour (GIST). In this study, patterns of recurrence after potential tumour seeding were investigated, and a new definition of tumour rupture, based on major and minor defects of tumour integrity, is proposed. Methods: Patients undergoing surgery for non‐metastatic small intestinal GIST from 2000 to 2012 were included in the study. Tumour spillage, tumour fracture or piecemeal resection, bowel perforation at the tumour site, blood‐tinged ascites, microscopic tumour infiltration into an adjacent organ, and surgical biopsy were defined as major defects of tumour integrity. Peritoneal tumour penetration, iatrogenic peritoneal laceration and microscopically involved margins were defined as minor defects. Results: Seventy‐two patients were identified. Median follow‐up was 58 (range 7–122) months. Radical surgery was performed in 71 patients. A major defect was recorded in 20 patients, and a minor defect in 21. The 5‐year recurrence rate was 64, 29 and 31 per cent in patients with major, minor and no defect respectively ( P  = 0·001). The hazard ratio (HR) for major defect versus no defect was 3·55 (95 per cent c.i. 1·51 to 8·35). Peritoneal recurrence rates for major, minor and no defect were 52, 25 and 19 per cent respectively ( P  = 0·002), and the HR for major defect versus no defect was 4·98 (1·69 to 14·68). On multivariable analysis, mitotic index, major defect of tumour integrity, tumour size and age were independently associated with risk of recurrence. Conclusion: Recurrence rates were increased after major, but not minor tumour ruptures. Abstract : A new classification